Inhibitory Effect of FMRFamide on NO Production During Immune Defense in Sepiella japonica - Zheng, Libing; Cao, Huimin; Qiu, Jiayin; Chi, Changfeng (Frontiers in Immunology, 2022)
Neuropeptide Phe-Met-Arg-Phe-NH2 (FMRFamide), specifically existing in invertebrates, plays pivotal roles in various physiological processes. The involvement in neuroendocrine-immune regulation was explored in recent years, and it could modulate nitric oxide (NO) production under immune stress. However, detailed knowledge is still little known. In this study, we identified FMRFamide as an inhibitory factor on NO production in the immune reaction of Sepiella japonica. Firstly, Vibrio harveyi incubation caused significantly upregulated expression of FMRFamide precursor and NO synthase (NOS) in just hatched cuttlefish with quantitative Real-time PCR (qRT-PCR), which indicated that both were likely to be involved in the immune defense. The whole-mount in situ hybridization (ISH) detected FMRFamide precursor and NOS-positive signals appeared colocalization, suggesting that at histological and anatomical levels FMRFamide might interact with NOS. Next, NOS mRNA was highly significantly upregulated at 72 h when FMRFamide precursor mRNA was knocked down effectively with the RNA interference (RNAi) method; the results hinted that FMRFamide was likely to regulate NO production. Continuously, the inflammatory model was constructed in RAW 264.7 cells induced by lipopolysaccharide (LPS), FMRFamide administration resulted in a highly significant reduction of the NO level in dose- and time-response manners. Although the addition of the selected inducible NOS (iNOS) inhibitor had inhibited the NO production induced by LPS, the additional FMRFamide could still furtherly sharpen the process. Collectively, it was concluded that neuropeptide FMRFamide could indeed inhibit NO production to serve as feedback regulation at the late stage of immune response to protect hosts from excessive immune cytotoxicity. The inhibitory effect on NO production could not only be mediated by the NOS pathway but also be implemented through other pathways that needed to be furtherly explored. The results will provide data for comparing the structure and immune function of neuroendocrine-immune system (NEIS) between “advanced” cephalopods and other invertebrates and will provide new information for understanding the NEIS of cephalopods.